مناظرات أحمد ديدات مع أهل الكتاب = Ahmad Didat de bate with the Christians and Jews - Elatrash, Radwan Jamal Yousef; Benadri, Farzana Bilali; Skookani, Najwa Nayf (The Islamic University College Journal, 2018)
This research aims to highlight the debates between Ahmed Deedat with the People of the Scripture (Jews and Christians) as Ahmad Deedat was keen to know their beliefs. This reflected in his relationship with them in the form of debate and dialogue. For instance, in his debate with Alqas Jimmy Swaggart at the University of Cutriana, his debate with Dr. Anis Shorrosh at the Arina Hall in Birmingham, England, and another two debates in Stockholm with the Archbishop; Stanley Schubert, as well as Professor Floridore Clark. The research used inductive and analytical methods and collect the data from ancient and modern sources on the subject to identify the new method in conducting dialogue with the People of the Scripture. At the end of this research, the researcher found that Ahmad Deedat has made excellent dialogues with the People of the Scripture that can benefit Muslim activists. *********************************************************** الملخّص:-اهتم أحمد ديدات بالمناظراته مع أهل الكتاب، وكانت علاقته معهم على شكلين المناظرة والحوار، وكان حريص في معرفة عقائدهم، ويهدف هذا البحث إلى إبراز مناظرات أحمد ديدات مع أهل الكتاب، من خلال مناقشة بعض المسائل الدعوية الواردة فيهما، وإظهار شخصية أحمد ديدات وقوة برهانه، في مناظرته مع القس جيمي سويجارت بقاعة جامعة كوتريانا، ومع أنيس شروش في قاعة أرينا في برمنجهام بإنجلترا، ومناظرتان في استكهولم مع كبير قساوسة السُويد إستانلي شوبيرج، كما ناظر البروفيسور فلوريد كلارك، وقد استخدم في البحث المنهج الاستقرائي والتحليلي وذلك من خلال جمع المعلومات من المصادر القديمة والحديثة المتعلقة بالموضوع، وتحليلها والاستفادة منها واستنباط سبل حوار حديثة مع أهل الكتاب. وخلصت البحث إلى أن أحمد ديدات تزخر مناظراته مع أهل الكتاب بفوائد للدعاة ويمكنهم الاستفاده منها.الكلمات المفتاحية: .